How Are Three Syntactic Types of Subordinate Clauses Different in Terms of Informational Weight? - Manon Lelandais; Gaëlle Ferré (Anglophonia)
Based on a video recording of conversational British English, this paper tests within the framework of Multimodal Discourse Analysis whether several different subordinate structures all express background information. Subordinate constructions have been described in syntax as dependent structures elaborating on primary elements of discourse. Although their verbal characteristics have been deeply analysed, few studies have focused on the articulation of the different communicative modalities in their production or provided a qualified picture of their informational input. Beyond showing that subordinate constructions express different types of prominence, the results suggest that the creation of focalisation mainly relies on gestural cues in these constructions. Changes in the modal configuration throughout the sequence suggest modalities are dynamic and flexible resources for expressing background or foreground information in subordinate constructions relatively to their syntactic type.